Évolution plutonique et structurale de la presqu' île d'Akuliaruseq, Groenland méridional. - Persoz, Francis (Meddelelser om Grønland, 1969)
The Akuliaruseq area, situated between Julianehåb and Nanortalik, is formed of granites (ea. 75% of the area) and gneisses belonging to the Canadian-Greenlandic shield. The geological history is divided into five periods of varying significance. The pre-Ketilidian is represented by the basement on which Ketilidian sediments were deposited. This basement was not recognised in the area under consideration, but has been identified to the north-west. The Ketilidian period comprises three major events : a) Deposition of supracrustal rocks. These were later metamrophosed in the amphibolite- ?granulite facies and migmatised, so that now they are represented by:- (top) A considerable thickness of homogeneous amphibolite, probably derived from volcanic rocks. A mixed suite of rocks of uncertain origin . Banded-homogeneous quartzites. Banded biotite-hornblende gneiss in the SW part of the area, and pelitic gneiss (with biotite, muscovite, andalusite, cordierite and (bottom) sillimanite) in the NE. b) Intrusion of gabbroic sills. This phase of intrusion, which predates the main deformation, is termed the first period of basic intrusion. c) Deformation and plutonism. The first phase of deformation resulted in subisoclinal and also overturned folds on NE axes. These were formed under plastic conditions. The second phase of deformation took place under less plastic conditions, and about NW axes. It resulted in several domes and basins formed mainly in the homogeneous amphibolites. Granitisation was continuous throughout the deformation though it reached a climax at the end of the first phase. The initial products were granodioritic in composition; successive episodes produced rocks more granitic in composition, ending with granite s. str. Syn- , late- and post-kinematic granites have been distinguished . III. The Kuanitic period. This corresponds to the second period of basic intrusion, which probably took place under anorogenic conditions. During this period two generations of dykes were emplaced, the earlier of which is ultrabasic, the later doleritic. At the beginning of the Sanerutian period the dykes of the second period of basic intrusion were folded, boudinee and granitised. They were competent in relation to the surrounding granites and gneisses which were partially reactivated and deformed but did not become strongly aggressive towards the basic dykes. This Sanerutian reactivation took place under amphibolite facies conditions. The next phase was characterised by the formation of numerous generations of aplitic and pegmatitic veins and by strong shearing at relatively high temperature. After the culmination of pegmalitisation came the third period of basic intrusion , during which the intrusion of several generations of dykes of gabbroic lo granodioritic composition alternated with, or occasionally was accompanied by, pegmatite development. The country granite did not become sufficiently mobile lo vein these dykes. Some of these dykes were emplaced into active shear zones, but the majority were deformed after their emplacement by intermittent movements which caused recrys tallisation and the formation of a schislosity in the dykes. The dykes behaved as incompetent bodies in the granites and gneisses. Owing to their close relations in time with plutonic events, these dykes are regarded as late-plutonic, and to some extent they are also syn-kinematic. At the end of the main phase of Sanerutian reactivation anorthositic rocks were developed, and also allochthonous porphyroblastic granites formed partially by intrusion and partially by replacement. The latter correspond to the Sydprøven granite group of WEGMANN (1938). Later, and after the intrusion of most of the third period basic dykes, a new generation of younger granites of autochthonous character was formed at the base of the homogeneous amphibolite. These granites originated by intense potash metasomatism preceded or accompanied by movements reactivating older structures. Basic dykes intruded these granites but were granitised by a late phase of activity in the granites. Still later dykes cut sharply across these autochthonous granites but were subsequently deformed and recrystallised. The Sanerutian period ended with the emplacement of a few rnicrogranites and the development of hot mylonites. The Gardar period is represented by several generations of dolerite dykes and many faults. No metamorphism or plutonism took place during or after this period. A chronological table is presented on p. 21.